GLOBALIZATION, COVID-19 PANDEMIC AND THE SITUATION IN AFRICA - ZEKERI MOMOH; JEREMIAH AKAHA GBENDA (International Studies Journal)
The outbreak of the Covid-19 pandemic in Wuhan, China, in December 2019 is closely linked to present global economic meltdown. Today, many African countries are still struggling to recover from the negative effects of the Covid-19 pandemic on their respective economy. Therefore, this study seeks to examine the influence of globalization on the spread of the Covid-19 pandemic and the situation in Africa.Moreover, secondary sources of data such as books, journals, and online resources was used for this study while content analysiswas used to analyse the data collected. However, this study is situated within the globalists perspective. The studyargues that globalisation contributed to the spread of the Covid-19 epidemic in Africa. This study argues that the Covid-19 virus spread from Wuhan in China, to other parts of the world within a very short time, due to movement of persons across international borders. The study also argues that many African countries' economies are currently experiencing extreme pressure, which has overstretched their economy. Lastly, the influence of globalisation on the spread of the Covid-19 cannot be overemphasised because it has significantly impacted on African states capacity to develop. As a result, African states should place more emphasis on the advantages of globalisation than on how it facilitates the spread oftheCovid-19Pandemic.